Letter: reproducible evidence shows that exclusive enteral nutrition significantly reduces faecal calprotectin concentrations in children with active Crohn's disease. Issue 11 (3rd November 2017) - Logan, M.; Ijaz, U. Z.; Hansen, R.; Gerasimidis, K.; Russell, R. K.
Abstract : Linked Content This article is linked to Swaminath et al and Feathers et al papers. To view these articles visithttps://doi.org/10.1111/apt.14253 andhttps://doi.org/10.1111/apt.14360 .